2016
DOI: 10.1186/s12884-016-0847-6
|View full text |Cite
|
Sign up to set email alerts
|

Why do some women choose to freebirth in the UK? An interpretative phenomenological study

Abstract: BackgroundFreebirthing or unassisted birth is the active choice made by a woman to birth without a trained professional present, even where there is access to maternity provision. This is a radical childbirth choice, which has potential morbidity and mortality risks for mother and baby. While a number of studies have explored women’s freebirth experiences, there has been no research undertaken in the UK. The aim of this study was to explore and identify what influenced women’s decision to freebirth in a UK con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 22 publications
0
53
0
2
Order By: Relevance
“…Research by Jackson et al [47] reports that women who free birth, do not view hospitals as safe places within which to birth. This view is further supported by other women who chose free birth in order to have choice, control and autonomy during birth [48] with some women relating the absence of the woman-centered care in maternity services, leaving them feeling vulnerable and unsafe [49]. It is important to note that safety relates not only to the physical sense of safety but also the emotional, psychological, and social aspects of care.…”
Section: No Midwifementioning
confidence: 99%
“…Research by Jackson et al [47] reports that women who free birth, do not view hospitals as safe places within which to birth. This view is further supported by other women who chose free birth in order to have choice, control and autonomy during birth [48] with some women relating the absence of the woman-centered care in maternity services, leaving them feeling vulnerable and unsafe [49]. It is important to note that safety relates not only to the physical sense of safety but also the emotional, psychological, and social aspects of care.…”
Section: No Midwifementioning
confidence: 99%
“…In our study the rejection of the biomedical model was a common theme that emerged as women's motivation to birth out of the hospital setting. Dahlen, Barclay and Homer (2010) as well as Feeley and Thomson (2016) reported that a medicalised care approach with routine interventions contributed to women's lack of satisfaction with previous births and to the drive to seek alternative birth places for subsequent pregnancies. Women who had a home birth felt that they were not bound to a biomedical model of care, which was the norm at the hospital (Laws et al, 2011).…”
Section: Empowerment and Self-determinationmentioning
confidence: 99%
“…A few women in our study had an unassisted birth after the birth they had experienced as traumatic. Although this might not be a course of action for all women with a traumatic birth experience, we know that this response is strongly associated with ascertaining human dignity, often a result of poor experiences with maternity care, a lack of faith in, and feeling unsafe with the care provided -due to the sense of loss of autonomy and the negative and disrespectful interactions with healthcare professionals [56]. These aspects seem to resonate with the experiences of the women in our study.…”
Section: Discussionmentioning
confidence: 57%